Pc=90√3
Pb=54√3
Pc=Pp+Pb
90√3=Pp+54√3
Pp=90√3-54√3= 36√3
[tex]\frac{a^{2} \sqrt{3} }{4}[/tex]=36√3 /×4
[tex]a^{2}[/tex][tex]\sqrt{3}[/tex]=144[tex]\sqrt{3}[/tex] /:[tex]\sqrt{3}[/tex]
[tex]a^{2}[/tex]=144 /√
a=12
Pb=3×[tex]\frac{1}{2}[/tex]×a×hb
54√3=3×[tex]\frac{1}{2}[/tex]×12×hb
54√3=18hb /:18
3√3=hb
[tex]H^{2}[/tex]+[tex](\frac{1}3}hp)^{2}[/tex]=[tex](3\sqrt{3})^{2}[/tex]
[tex]H^{2}[/tex]+([tex]\frac{1}{3}[/tex]×[tex]\frac{12\sqrt{3} }{2})^{2}[/tex]=27
[tex]H^{2}[/tex]+([tex]\frac{6\sqrt{3} }{3})^{2}[/tex]=27
[tex]H^{2}[/tex]+[tex](2\sqrt{3}) ^{2}[/tex]=27
[tex]H^{2}[/tex]=27-12
[tex]H^{2}[/tex]=15
H=[tex]\sqrt{15}[/tex]
V=[tex]\frac{1}{3}[/tex]×Pp×H
V=[tex]\frac{1}{3}[/tex]×36√3×√15= 12√3×√15=12√45=36√5